Tindak Tutur Dalam Cerpen Bengawan Solo Karya Danarto (Sebuah Tinjauan Pragmatik) - Fakhri Maulana Firjatullah; Nopira Aulia Rahmah; Irwan Siagian (Journal on Education, 2023)
Literary works, especially short stories, are products that are produced based on one's experiences and observations in life. This makes short stories very interesting to study from the perspective of various scientific disciplines, especially pragmatics. In this regard, this study aims to determine the forms of speech acts used by the characters in Danarto's Bengawan Solo short story. This research is a qualitative research using descriptive method using note-taking technique as a data collection technique and content analysis technique as an analysis technique. Based on the results of this study, 18 data of locutionary acts, 27 data of illocutionary acts, and 5 data of perlocutionary acts were found by the researcher. As a result, the findings that the researchers found totaled 50 findings in total. The findings include: 18 types of locutionary speech acts or as much as 36%, 27 types of illocutionary speech acts or as much as 54%, 5 types of perlocutionary speech acts or as much as 10%.